JARINGAN SOSIAL ANTARA PETANI DAN PEDAGANG SAYUR DI PASAR TRADISIONAL BANGKINANG - Agustin, Rahmi Rahmaini; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Langgini Village, Bangkinang Sub-District, Kampar Regency. The problem studied is how the range of social networks developed between farmers and vegetable traders? and What is the background of the growing trust between farmers and vegetable sellers? The objective of the study was to determine the range of networks developed between farmers and vegetable traders also, to analyze what the background of the emergence of trust between farmers and vegetable sellers in Bangkinang market. The sample used in this research is Simple Random Sampling, technique in this research are 40 vegetable farmers and 20 vegetable sellers. Researchers use the theory of social capital, Theory used is social capital theory where there must be trust, network and norm. The results of general research conducted then the authors can say that there are three forms of network formed in the market Bangkinang is a long, medium and low network range. The author uses the method of Quantitative Deskriftif.Keywords: Network, Farmer, Trader, Trust.